ANÁLISE BIBLIOMÉTRICA SOBRE A UTILIZAÇÃO DE RESÍDUOS NO MELHORAMENTO DO SOLO PARA PAVIMENTAÇÃO - Teixeira, Wagner; Cardoso, Alexandre; Iarozinski Neto, Alfredo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The industrial sector waste generation is exponential and increases every year, it is sought to reuse the waste in order to improve or create a characteristic of a raw material. In response to the high volume of waste generated, the country is facing a financial crisis, scarcity of natural resources and a need for new technologies in infrastructure works. Through the bibliometric analysis, we list the most applied residues, of which segment, less waste and residues that do not fit the geotechnical aim. An appropriate search string was created to obtain a RIS (Research Information Systems) file, and thus through VOSviewer software, to obtain a bibliometric mapping of the waste under study in the area of geotechnical engineering of pavement. From the bibliometric map was defined 3 groups (clusters) with a minimum number of keywords in 5 occurrences. From the map it is analyzed which materials and which segments are under study by the academic community. The interpretation of the results shows that in the first cluster predominate materials derived or directed to the civil construction. Cluster number 2 encompasses industrial materials. The third cluster involves industrial materials and elements of chemical analysis.